HEDGING STRATEGIES IN MANAGING UNCERTAINTY: THE ROLE IN UZBEKISTAN'S TRANSITION TO IFRS - Master's Degree Marupov Abdushukurbek Alijonovich; Undergraduate Student Kamoliddinov Sherzodbek (European Science Publishing, 2024)
This article examines the role of hedging strategies in managing uncertainties during Uzbekistan's transition to International Financial Reporting Standards (IFRS), as mandated by Presidential Decree No. 4611 on February 24, 2020. The decree emphasizes the importance of adopting IFRS to provide transparent financial information and enhance access to international financial markets. The article explores how hedging strategies contribute to financial stability and transparency during this transition.
Keywords: IFRS Transition, Hedging Strategies, Financial Reporting, Uzbekistan, Forward Contracts, Options, Futures Contracts, Swaps, Financial Stability, Risk Management, Presidential Decree No. 4611.